Liability Structure in Small-Scale Finance : Evidence from a Natural Experiment - Carpena, Fenella; Cole, Shawn; Shapiro, Jeremy; Zia, Bilal (Oxford University Press on behalf of the World Bank, 2015)
Microfinance, the provision of small individual and business loans, has experienced dramatic growth, reaching over 150 million borrowers worldwide. Much of the success of microfinance has been attributed to attempts to overcome the challenges of information asymmetries in uncollateralized lending. However, very little is known about the optimal contract structure of these loans; and there is substantial variation across lenders, even within a particular setting. This paper exploits a plausibly exogenous change in the liability structure offered by a microfinance program in India, which shifted from individual to group liability lending. We find evidence that the lending model matters: for the same borrower, the required monthly loan installments are 11 percent less likely to be missed under the group liability setting in comparison with individual liability. In addition, compulsory savings deposits are 20 percent less likely to be missed under group liability contracts.